Estudo toponímico bilíngue (português e libras) das instituições de ensino públicas e privadas de Feira de Santana - Dantas, Emanuelle Reisurreição Santos Carneiro (2024)
Toponymy is part of the lexical sciences as a branch of Onomastics and, within these studies, it deals with the investigation of the proper names of places. The process of naming places is common to all languages, which is why this action is also verified in Libras, through the attribution of signs to spaces. Therefore, this dissertation aims to analyze the toponymic motivations behind the naming of public and private educational institutions in the city of Feira de Santana in Portuguese and in Libras. This study is part of the agenda of the research project Bilingual study of the toponymy of Feira de Santana-BA: Portuguese-Libras, developed at UEFS. The research is based on the theoretical assumptions of Lexicology and Modern Lexicography (Biderman, 1984; 1998; 2001; Vilela, 1983; Barreiros, L., 2017), Toponymy (Dick, 1987; 1990; 1992; Seabra, 2004; 2006), toponymic studies in Libras (Sousa, 2017; 2019; 2021; 2022) and linguistic studies in Libras (Souza Júnior, 2012; Karnopp, Quadros, 2004; Quadros, 2019). The research corpus consists of 46 educational toponyms, organized into the following categories: municipal schools (5), state schools (8), teaching centers (3), federal institute (1), public universities (3), private schools (19), private universities and colleges (5) and philanthropic educational institutions (1). The proposal of lexicographic-toponymic records used in similar studies (Ferreira, 2019; Jesus, 2019; Marins, 2024) is adopted for the systematization and analysis of data. Through qualitative and quantitative analysis of the data collected, the results allowed us to verify that most of the denominations of educational institutions in Feira in Portuguese belong to the class of anthropotoponyms (toponyms relating to proper names), in contrast in Libras the predominance is of mimetoponyms (names generated from mimetic processes, that is, motivation presented with a high degree of iconicity), in this way the discussion reaffirms the inseparable relationship between language, culture and society. The results also reveal the importance of toponymic research for recovering and recording the history and culture of Feira for both communities (deaf and hearing). Finally, the signs in Libras of the toponyms studied are available to the public in a digital inventory created from the Instagram @educatopos.